2017
DOI: 10.1088/1361-648x/aa57ac
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of LaAlO3/SrTiO3n-type interfaces: a GGA+Ustudy

Abstract: The role of electronic correlation effects for a realistic description of the electronic properties of [Formula: see text]/[Formula: see text] heterostructures as covered by the on-site Coulomb repulsion within the GGA+U approach is investigated. Performing a systematic variation of the values of the Coulomb parameters applied to the Ti 3d and La 4f orbitals we put previous suggestions to include a large value for the La 4f states into perspective. Furthermore, our calculations provide deeper insight into the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…That is why in this study we have employed the GGA+U approach for the d-orbitals of Ti and Fe. The value of U for Ti was estimated to be 8.0 eV by reproducing the optical band of SrTiO 3 , 3.2 eV, and comparing with data from the literature [ 26 ]. The value of U for Fe, 3.0 eV, is taken from the literature where it was optimized for SrFeO 3 [ 27 ].…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…That is why in this study we have employed the GGA+U approach for the d-orbitals of Ti and Fe. The value of U for Ti was estimated to be 8.0 eV by reproducing the optical band of SrTiO 3 , 3.2 eV, and comparing with data from the literature [ 26 ]. The value of U for Fe, 3.0 eV, is taken from the literature where it was optimized for SrFeO 3 [ 27 ].…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…The ab initio calculations were based on DFT [4] in the framework of the GGA+U method, with additional local correlations of U = 2 eV to the Ti 3d orbitals and U = 8 eV to the La 4f orbitals [5]. We used Vienna Ab-Initio Simulation Package (VASP) [6], which is part of the MedeA R software of Materials Design.…”
Section: Resultsmentioning
confidence: 99%
“…To study the heterostructure with defects, we used 2 × 2 in-plane supercells of the bare heterostructures [7] with introduced oxygen vacancies and hydrogen dopants at the surface, or in an interfacial layer on both sides while preserving the inversion symmetry of the slabs. More details about computation parameters and slab geometry can be found in [5,7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the U−J parameters were added to La 4f, Ti 3d and Mn 4d (U=8 eV, 2 eV and 4 eV, respectively). This choice was based on our previous detailed investigation of the effect of local electronic correlations as captured by the GGA+U method [39], as well as [40]. In ourprevious study of U effect on the LaAlO 3 /SrTiO 3 system we have concluded that U parameter is important and it affects quantitatively the band gap.…”
Section: Methodsmentioning
confidence: 99%